Consequences of human-mediated rodent invasions on the epidemiology and population structure of Toxoplasma gondii : the example of Senegal - (:unkn) unknown (My University, 2018)
Toxoplasma gondii is a ubiquitous zoonotic protozoan capable of infecting all homeotherms including humans. A marked geographical contrast has been noted at the global scale concerning the genetic diversity and pathogenicity in humans of strains of this parasite. A growing number of studies show the importance of considering the influence of strain factor in the study of the epidemiology of human toxoplasmosis. However, genetic diversity data remain very limited for large regions of the world including Asia and Africa. Also, the determinants of the spatial structure of T. gondii populations worldwide remain poorly understood. During this work, we were interested in the influence of human exchanges on the evolution of parasite populations in Africa, and more particularly in Senegal. Our results support an important role of invasive rodents that accompany human exchanges in the introduction of strains at the port areas of the country through maritime trade. Our results also suggest a role of the invasive mouse Mus musculus domesticus in the counterselection of the clonal lineage Africa 1, the predominant lineage of T. gondii in West Africa. These new elements shed light on some of the mechanisms that shape T. gondii populations. Further studies in different epidemiological situations, combined with experimental studies, will be needed to accurately measure the influence of these host parasite interactions on the epidemiology of toxoplasmosis.
Keywords: African Research